Pengaruh Revitalisasi Alun-alun Dadaha terhadap Pertumbuhan Sosial Ekonomi Wilayah Tasikmalaya - Stefanny Tri Angelika; Siti Fadjarajani; Cahya Darmawan (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The revitalization of Dadaha Square in Tasikmalaya City has had a significant positive impact on the social and economic growth of the local area. Socially, this revitalization has succeeded in enhancing interactions among residents, creating a more inclusive environment, and supporting various community activities such as sports, arts, and recreation. Additionally, it has strengthened the collective identity of the community. Economically, the revitalization of Dadaha Square has provided new opportunities for small and medium enterprises (SMEs), with an increased number of visitors positively affecting the growth of the informal economy, particularly for street vendors. This positive impact also contributes to the growth of the tourism and service sectors in Tasikmalaya City. However, the sustainability of these benefits requires effective public space management and appropriate regulatory support for informal economic actors. Further studies are needed to monitor the long-term effects of this revitalization.